Reinventing The University Literacies and Legitimacy in the Postmodern Academy - Schroeder, Christopher (University Press of Colorado, 2001)
Christopher Schroeder spends almost no time disputing David Bartholomae's famous essay, but throughout ReInventing the University, he elaborates an approach to teaching composition that is at odds with the tradition that essay has come to represent. On the other hand, his approach is also at odds with elements of the pedagogies of such theorists as Berlin, Bizzell, and Shor. Schroeder argues that, for students, postmodern instability in literacy and meaning has become a question of the legitimacy of current discourse of education. Schroeder is committed, then, to constructing literacies jointly with students and by so doing to bringing students to engage more deeply with education and society.